2019
DOI: 10.1536/ihj.19-110
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence of Sudden Deaths and Heart Diseases in Fukushima After the Great East Japan Earthquake

Abstract: On March 11, 2011, a great earthquake, known as the Great East Japan Earthquake, hit northeastern Japan, resulting in a tsunami that caused a nuclear disaster, the Fukushima Daiichi Nuclear Power Plant accident, forcing about 160,000 people to evacuate. We, therefore, sought to examine the effects of this evacuation on the onset of cardiovascular diseases and sudden death (SD) in Fukushima Prefecture, three years after the earthquake. We divided the evacuation zone into two areas, whole evacuation zone (Area 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The association between IHD and geophysical disasters (including earthquakes, volcanic activity and PLOS ONE mass movements) has been well studied. Takiguchi et al [16] reported significantly increased long-term (3-year) rates of mortality due to acute myocardial infarction (AMI) in both men and women after the Great East Japan Earthquake (2011, Japan). Similar findings were reported by Nakagawa et al [17] after the Niigata-Chuetsu earthquake (2004, Japan).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The association between IHD and geophysical disasters (including earthquakes, volcanic activity and PLOS ONE mass movements) has been well studied. Takiguchi et al [16] reported significantly increased long-term (3-year) rates of mortality due to acute myocardial infarction (AMI) in both men and women after the Great East Japan Earthquake (2011, Japan). Similar findings were reported by Nakagawa et al [17] after the Niigata-Chuetsu earthquake (2004, Japan).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Furthermore, studies have shown a significant increase in overall mortality rates from acute myocardial infarction in disaster areas after earthquakes [ 5 , 6 ]. In addition, other studies found that the magnitude of a disaster, as well as related stress and population aging, may lead to a temporary increase in the incidence of sudden cardiac and unexpected death [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…People who were forced to leave their homes were more likely to develop post-traumatic stress disorder [9,10], and approximately 4.7% of the residents in the Fukushima Prefecture lost or changed their job [11]. Previous studies have also shown that evacuees had higher risks of diabetes, heart disease, and sudden cardiac death [12,13] than non-evacuees.…”
Section: Introductionmentioning
confidence: 99%